Effects Of Online Gaming Addiction On Adolescent Physical Health - Wibowo, Syifa Sofia; Belladiena, Alfiena Nisa (Jurnal Riset Kesehatan, 2024)
In all of Southeast Asia, Indonesia has the most gamers. It is estimated by the Indonesian government that 2.7 billion individuals suffer from gaming addiction. APJII (Indonesian Internet Service Providers Association) data indicates that 89.9 billion people play online games on their mobile phones, and this number is predicted to rise. The purpose of this study is to analyze relationship between online gaming addiction with adolescent physical health. Analytical research using a cross-sectional design. The study was carried out between December 1–8, 2023, in one of Semarang City's private high schools. There are 198 students and divided up among 6 distinct classes. 66 students from 6 classes were the sample size for the sampling procedure, which employed the Slovin formula. This study uses basic random sampling or draws based on the number of attendance. The GAS (Game Addiction Scale) questionnaire sheet and the respondent's physical health questionnaire were employed in the data collection procedure. Using Pearson Product Moment correlation for data analysis. Playing online games can have an impact on an adolescent's physical health and between two variables have a strong association